Relationship of Food Hygiene with Patient Satisfaction in Royal Prima Hospital - Pretty Grace Zalukhu; Zulfendri; Albiner Siagian (Britain International of Exact Sciences (BIoEx) Journal, 2020)
The aim of the study is want to find out Relationship of Food Hygiene with Patient Satisfaction. This type of research is analytic survey research with cross sectional study approach that is by measuring or observing at the same time (once in a while) between the dependent and independent variables. The dependent variable in this study is patient satisfaction, while the independent variable is the quality of food delivery services. The result shows that food hygiene is related to satisfaction of inpatients. If the food hygiene is good, the patient is probably 2.8 times more satisfied than those who claim to be bad.